Research of the influence of tire hydroplaning on directional stability of vehicle - Sapragonas, Jonas; Keršys, Artūras; Makaras, Rolandas; Lukoševičius, Vaidas; Juodvalkis, Darius (Transport, 2013)
Vehicle use is inherently linked to the risks. While transport means are being constantly improved, active and passive safety issues appeared to be more and more complex what makes experimental testing and numerical modelling problems of safety – sensitive structures considerably actual. In case of hydroplaning phenomenon to keep the vehicle’s stable direction its movement becomes more difficult. Selection of the safe speed is one of the main objectives in order to ensure greater traffic safety and reduce the possibility of an accident. The aspects of tire simulation by finite element method were revealed and analysis of the impact of a vehicle’s speed on the appearance of hydroplaning process was performed. The peculiarities of Euler–Lagrange formulation of dynamical problems and modelling of fluid – structure interaction by finite element method are presented in the research. The article describes preliminary models developed using the PATRAN and DYTRAN software packages. On the basis of these models, numerical calculations have been performed, in consequences the values of critical speed of the tire hydroplaning was obtained. First Published Online: 24 Dec 2013